My own nikkei identity - Higa, Ana María (2020)
The Nikkei concept is reviewed within the peruvian sociocultural context, by her own life experience, to explore her origin from her grandparents, who came from Okinawa Island as a migrants, by the early 20th century, she make the building memories by herself, about her parents, and her life experience in transit from Huaral, Callao and Lima. Some singular figure of her life is offered, since the early childhood, school age , go through to the university and the professional interaction, when she understood the value to have and maintain her own Nikkei identity within the japanesse culture, in convivence to the Peruvian culture .